Análise dos comportamentos de aproximação e retraimento de pré-termos de risco evidenciados em uma unidade de terapia intensiva neonatal - FARIAS, Gabriela Ribeiro Barros de (2006)
Care taking in neonatology has been increased in the last years concerning the conditions of prematurity and low weight at birth, specially related to health, growth and development of children who are under such a condition of risk. One of the most relevant points of neonatology researches is about the behavioral observation of signs emitted by the premature organism work, which possibly reveal the level of organization or disorganization of the organism as a whole, making it possible to predict future harms. Since 1978, an American researcher , Heidelise Als, with a group of collaborators, has started several researches about the behavior and assistance to low weight premature babies which do emphasize a differential care practice to their development using as a base the Syncronic Active Theory of Development (SATD), which has enabled the registration and elaboration of individualized care in order to promote the development of premature babies, reflecting gains for an effective development of the different functions of the organism, mainly in the motor cognitive and behavioral areas. Hence, this paper has the aim to quantify those behaviors which are more evident in the context of a Neonatology Intensive Care Unit (NICU), and what the environmental mechanisms which favor their manifestations are, in order to track down the cares to development according to the reality present in the NICU. The research has been planned through a pre-project which has enabled the registration in 19 samples of children to 30 sections of observation, being developed in the period of April to June, 2005. Data collection has been performed in premature babies with low weight at birth and with fetus age between 26 to 37 weeks. Such collection has used a standard etogram based on behavioral observation of H.Als, marking the environmental events that had promoted some behaviors. The observation was performed in a period of 15 minutes per individual of such sample. The tabulated data resulted in general data through maternal and babies variables and through specific data of behaviors and environmental interferences. The general data have kept a similarity with other researches, pointing out unfavorable social conditions and maternal predisposition to infections as possible predisposition factors to a premature delivery as well as the prematurity situation as a worsening event of the babys health and welfare. Among the specific data, it was possible to register a prevalence of restraint behaviors which do reveal the babys disorganization facing the excess of environmental interferences, such as noises, manipulation and luminosity, much common in NICUs. Eventually, through such facts, we suggest into this research possible solutions to ease the excess of disorganizing behavioral manifestations, trying to make a priority to the cares of the development through practices already used by H.Als and her team.